1969
DOI: 10.1002/jsfa.2740200514
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on cellulose digestion under in vitro conditions

Abstract: The extent of cellulose digestion by rumen micro‐organisms in vitro is dependent on the pH of the medium. Digestion is greatly reduced at pH values similar to those found within the rumen of sheep fed with diets rich in readily digestible carbohydrates. It is suggested that this may be one of the reasons for reduced digestion of the fibre component of forages when carbohydrate supplements are fed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(37 citation statements)
references
References 10 publications
3
33
0
Order By: Relevance
“…In this case, the association with concentrate probably reduced the digestibility of the fiber fraction of the roughage. The greater supply of nonfiber carbohydrates may reduce the fiber digestion by its inhibitory effect on cellulolysis or by inhibiting the sites of enzymatic digestion in the fibers, according to Terry et al (1969) and Murphy (1989).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the association with concentrate probably reduced the digestibility of the fiber fraction of the roughage. The greater supply of nonfiber carbohydrates may reduce the fiber digestion by its inhibitory effect on cellulolysis or by inhibiting the sites of enzymatic digestion in the fibers, according to Terry et al (1969) and Murphy (1989).…”
Section: Discussionmentioning
confidence: 99%
“…The increased concentration of acetate and propionate in silage mixtures containing high level of AF may be due to the higher CP content which leads to a more favorable fermentation environment (pH, NH 3 ) for growth of cellulolytic bacteria. Other researchers have showed that cellulolytic bacterial population could significantly increased by higher ruminal NH 3 (Khampa et al, 2006;Vinh et al, 2011) and the cellulolytic activity of rumen contents could be markedly inhibited by a fall of pH (Terry et al, 1969;Stewart, 1977) because of their influences on the rumen ecology. Higher ruminal NH 3 level may serve as N source to improve rumen ecology (Wanapat and Pimpa, 1999).…”
Section: In Vitro Rumen Degradability and Fermentation Of Ss-af Silagmentioning
confidence: 97%
“…In addition, rumen pH is one of the most critical determinants for rumen function as cellulolytic bacteria fail to grow below pH 6.0. While, early studies have reported that low rumen pH has negative effects on appetite (Shinozaki, 1959), microbial yield (Oliveira et al, 1997;Russell and Dombrowski, 1980), methane production (Lee et al, 2003), dry matter intake (Dewhurst et al, 2001), milk yield (Wanapat et al, 2009) and fiber digestion (Smith et al, 1973;Stewart, 1977;Terry et al, 1969).…”
Section: Resultsmentioning
confidence: 99%